PSIDIUM GUAJAVA LEAVES COMPOUND AS ANTI-INFLAMMATION: SYSTEMATIC REVIEW - Angela Librianty Thome; I Ketut Sudiana; Abu Bakar (Jurnal Natural, 2019)
Psidium guajava leaves are plants that have been widely used to treat health problems, such as inflammation. Guava leaves are one of the parts used in this plant. People use guava leaves because it can be reached and has minimal side effects. The aim of this study was to identify the content available in guava leaves and their bioactivity as anti-inflammatory. The design of this study uses systematic reviews. Article are taken from electronic databases such as Scopus, Pubmed, ProQuest, and Science Direct. Articles are taken from 2013 to 2019 with the keywords “phytochemical” OR “chemical” OR “compounds” AND “psidium guajava leaves” AND “anti-inflammation”. The review results of 3 articles explained that guava leaves contain ingredients that can be useful as anti-inflammatory. Guava leaves provide a great effect or benefit to inflammation.